PEMASARAN TAHU DI INDUSTRI RUMAH TANGGA MATOWARI KELURAHAN PANIKI BAWAH KECAMATAN MAPANGET SULAWESI UTAR - David Hebingadil; Juliana R. Mandei; Joachim N.K. Dumais (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The objective of this research is to develop tahu business in Matowari Home Industry in Paniki Bawah Village, Mapanget Subdistrict. This research was conducted for three months from December 2018 to February 2019 which began from preparation to reporting of research. Paniki Bawah is located at an altitude of approximately 65 meters above the sea surface. Paniki is under the status of kelurahan, and currently has an area of more than 780 hectares, consisting of 10 (ten) neighborhoods, with a population of 2,783 households, a population of 9,679 people. Namely sampling in the same way and the determination of the Marketing Institution sample using the snowball sampling method. The research result of this study indicated that there are two patterns of marketing know-how, namely. Marketing channels I from producers to consumers and marketing channels II from producers to retailers then from retailers to end consumers. In channel I there is no marketing cost, but in marketing channel II there is a marketing fee of Rp. 39.8 per piece. Total profit of Rp. 135 pieces. Total marketing margin of Rp. 175 per piece of tahu.Keywords: Marketing, tahu, home industry